Case Report: Novel ADA2 variants cause atypical adenosine deaminase 2 deficiency - Haishao Yu; Haishao Yu; Shuangzhu Lin; Lin Li; Jiayi Li; Qiandui Chen; Yuheng Wu; Yangfan Qi; Wanqi Wang; Xingzhi Chang; Jie Zhang (Frontiers in Genetics)
Case presentationA girl aged 2 years and 5 months presented to the hospital with chief complaints of intermittent fever and weakness of the left limb for more than 1 month. The child had transient urticaria appearing on her face for 5 days. The inflammatory biomarkers were significantly increased. Brain MRI showed multiple ischemic lesions in the brain’s small vessels. The patient exhibited significant systemic inflammation and multiple vasculitis. Whole-exome sequencing showed c.1358A>G p. (Tyr453Cys) and c.1082-7T>A compound heterozygous variants in the adenosine deaminase 2 (ADA2) gene, of which the c.1082-7T>A variant has not been reported yet in previous literature. Peripheral blood mRNA reverse transcription-Sanger sequencing confirmed that this variant affected mRNA splicing, resulting in a frameshift with premature stop codon c.1083_1103del p. (Leu362Glnfs*45). Peripheral blood test suggested a significant decrease in ADA2 activity. Eventually, the patient was diagnosed with deficiency of adenosine deaminase 2 (DADA2). Her condition improved after treatment with etanercept. She had no more fevers, and no hemiplegia attacks were observed during the 3 years of follow-up.ConclusionFever and hemiplegia were the main manifestations in this patient, without typical rashes. DADA2 was finally confirmed by enzymology and genetic testing, and we believe this is the first reported case of the c.1082-7T>A intronic variant in DADA2, and the RNA studies conducted in this case have been pivotal in assessing its pathogenicity.